KOMUNIKASI DAKWAH MELALUI MEDIA SOSIAL - Dudung Abdul Rohman (Tatar Pasundan: Jurnal Diklat Keagamaan, 2019)
Today preaching activities through social media are very widespread and attract the attention of all parties. So that prachers are popular on social media whom can shifting the preachers conventionally popular among the people. Then came the social media such as Ustadz Abdul Somad, Adi Hidayat, and Evie Effendi. In this case, it is certainly interesting to examine da'wah communication activities through social media. The research method used is qualitative-descriptive which seeks to describe how da'wah communication activities through social media that have been going on so far. While the data collection technique uses library research that uses relevant books as primary and secondary data sources. This research produces a picture, that da'wah communication activities through social media are related to patterns of social interaction, persuasive patterns, and ethos factors or the attractiveness of da'wah activities through social media. If da'wah activities through social media want to be effective and interesting, then they must pay attention to these patterns well. This has been proven by Ustadz Abdul Somad, Adi Hidayat and Evie Effendi in his missionary communication activities through social media. Their da'wah activities are seen as effective and attractive, because they pay attention to patterns of social interaction, persuasive patterns, and ethos and attractiveness in the missionary activities.Key Words: Communication; Islamic preaching; Social media